Prevalence and Genetic Diversity of Legionella spp. in Hotel Water-Supply Systems in Latvia - Olga Valciņa; Daina Pūle; Juris Ķibilds; Andžela Lazdāne; Jūlija Trofimova; Svetlana Makarova; Genadijs Konvisers; Laima Ķimse; Angelika Krūmiņa; Aivars Bērziņš (Microorganisms, 2023)
Legionella is one of the most important waterborne pathogens that can lead to both outbreaks and sporadic cases. The majority of travel-associated Legionnaires’ disease (TALD) cases are contracted during hotel stays. The aim of this study was to evaluate the prevalence and genetic diversity of Legionella spp. in hotel water supply systems in Latvia. In total, 834 hot water samples were collected from the water systems of 80 hotels in Latvia. At least one Legionella spp. positive sample was detected in 47 out of 80 hotels (58.8%). Overall, 235 out of 834 samples (28.2%) were Legionella spp. positive. The average hot water temperature in Latvian hotels was 49.8 °C. The most predominant L. pneumophila serogroup (SG) was SG3 which was found in 113 (49.8%) positive samples from 27 hotels. For 79 sequenced L. pneumophila isolates, 21 different sequence types (ST) were obtained, including 3 new types—ST2582, ST2579, and ST2580. High Legionella contamination and high genetic diversity were found in the hotel water supply systems in Latvia, which, together with the insufficient hot water temperature, may indicate that the lack of regulation and control measures may promote the proliferation of Legionella.